Analysis of the Clinical Features of Intrauterine Ureaplasma urealyticum Infection in Preterm Infants: A Case-Control Study - Tong Sun; Jianhua Fu (Frontiers Media S.A., 2021)
Objective: To analyze the clinical characteristics of intrauterine Ureaplasma urealyticum (UU) infection in premature infants.Method: In this single-center retrospective case-control study, 291 preterm infants born in our hospital and hospitalized in our department and gestational age no more than 32 weeks, birth weight no more than 2000 g were included from January 2019 to January 2021. Lower respiratory tract secretion, gastric fluid and urine were collected for UU RNA detection within 48 h after birth. Intrauterine UU infection is defined by at least one positive UU-PCR test of secreta or excreta of preterm infants after birth. The UU infection group included 86 preterm infants and the non-UU infection group included 205 preterm infants. We compared their clinical features, hemogram changes and disease outcomes using statistical analyses.Results: The clinical characteristics of premature infants such as the duration of oxygen use and ventilator use in hospital were significantly prolonged in the UU infection group (P < 0.05). The levels of leukocytes, platelet and procalcitonin in the UU infection group were significantly higher than in the non-UU infection group (P < 0.05). In terms of preterm complications, only the incidences of bronchopulmonary dysplasia, retinopathy of prematurity and metabolic bone disease in premature infants in the UU infection group were significantly higher than those in the non-UU infection group (P < 0.05). The mode of delivery, maternal premature rupture of membranes, and postnatal leukocyte level were independent risk factors for UU infection, while gestational hypertension was a protective factor for UU infection. The level of leukocytes in postnatal hemogram of premature infants could be used as a diagnostic index of UU infection, but the diagnostic accuracy was poor.Conclusion: In our study, UU infection can increase the incidence of bronchopulmonary dysplasia, retinopathy of prematurity and metabolic bone disease in preterm infants, but have no effect on the incidence of necrotizing enterocolitis, intracranial hemorrhage, white matter damage and other diseases in preterm infants. For high-risk premature infants, UU should be detected as soon as possible after birth, early intervention and drug treatment necessarily can improve the prognosis as much as possible.